Structure of the hexagonal surface layer on Caulobacter crescentus cells - Bharat, T; Kureisaite-Ciziene, D; Hardy, G; Yu, E; Devant, J; Hagen, W; Brun, Y; Briggs, J; Löwe, J (Springer Nature, 2017)
Many prokaryotic cells are encapsulated by a surface layer (S-layer) consisting of repeating units of S-layer proteins. S-layer proteins are a diverse class of molecules found in Gram-positive and Gram-negative bacteria and most archaea1-5. S-layers protect cells from the outside, provide mechanical stability and also play roles in pathogenicity. In situ structural information about this highly abundant class of proteins is scarce, so atomic details of how S-layers are arranged on the surface of cells have remained elusive. Here, using purified Caulobacter crescentus' sole S-layer protein RsaA, we obtained a 2.7 Å X-ray structure that shows the hexameric S-layer lattice. We also solved a 7.4 Å structure of the S-layer through electron cryotomography and sub-Tomogram averaging of cell stalks. The X-ray structure was docked unambiguously into the electron cryotomography map, resulting in a pseudo-Atomic-level description of the in vivo S-layer, which agrees completely with the atomic X-ray lattice model. The cellular S-layer atomic structure shows that the S-layer is porous, with a largest gap dimension of 27 Å, and is stabilized by multiple Ca2+ ions bound near the interfaces. This study spans different spatial scales from atoms to cells by combining X-ray crystallography with electron cryotomography and sub-nanometre-resolution sub-Tomogram averaging.